Desmoplastic infantile ganglioglioma: Report of an unusual case with a cranial defect - Basaran, Recep; Cakir, Fatma Betul; Isik, Nejat; Sav, Aydin; Elmaci, Ilhan (MEDKNOW PUBLICATIONS \& MEDIA PVT LTD, 2014)
Desmoplastic infantile ganglioglioma (DIG) is a rare tumor that typically occurs in infants under the age of 24 months. These tumors commonly have a good prognosis after surgical resection despite their aggressive radiological appearances. Clinical signs are due to the large size of the tumor and include increased head circumference, bulging fontanel, sunset sign and seizures. We report an unusual DIG case who presented with parietal bulging associated with a bony defect. The patient was thought to have a leptomeningeal cystic formation, but on his cranial magnetic resonance imaging (MRI), we observed a centrally and homogeneously gadolinium-enhanced lesion fixed to the dura by its solid component. A surgical gross total resection was performed, and no residual tumor was observed on follow-up.
Keywords: Bony defect; desmoplastic; ganglioglioma; pediatric; skull deformation; supratentorial tumor